Morte celular programada em microalgas verdes cocoides e seus possíveis efeitos ecológicos - Barreto Filho, Marcelo Malisano (2020)
Programmed cell death may have important intra and inter-specifics effects in phytoplanktonic populations, and consequently in the ecology of freshwater ecosystems. However, before any ecological studies or evolutionary interpretations, it is essential to document the phenotypic changes associated with PCD since the morphotypes and markers may be different in the same organism in response to different environmental stimuli, implying in different ecology evolutionary interpretations. Moreover, these interpretations can also be conflicting due to incorrect application and interpretation of the measures and markers of PCD. Thus, in Chapter 1, we presented a systematic review of the different methods and measures of PCD, and offered suggestions as how PCD should be measured in eukaryotic phytoplankton. Additionally, in chapter 2 we provided a first-time report of PCD in Ankistrodesmus densus, a member of the important microalgal group of the family Selenastraceae (Chlorophyta, Chlorophyceae, Sphaeropleales). Based on our revision, transmission electron microscopy (TEM) appears essential, as the first approach, for properly detecting PCD. Ultrastructural images should be compared and complemented with biochemical and genetic assays. In order of preference, we suggested DNA laddering and PS externalization. Biochemical markers such as caspase activity and the increase in reactive oxygen species (ROS) should be used with caution since these are not specific enough for PCD. Therefore, we have used ultrastructural morphological changes, PS externalization and DNA laddering to document PCD in A. densus in response to darkness, nitrogen starvation, and heat and cold shock. Our findings suggest that light and nitrogen deprivation may lead to a small but significant fraction of community to undergo PCD. On the other hand, we also present evidence that different death morphotypes can emerge in A. densus depending on different environmental inducers, which is essential for the interpretation of the results of ecological studies. Moreover, our results indicate that the vacuolar/autophagic like cell death morphotype existed in single-celled green microalgae (Chlorophyta) before land plants evolved and might have been an important development for tissue homeostasis in higher multicellular plants.